Preliminary investigations on novel camphor-derived chiral sulfones: completely stereoselective formation of tricyclic ?-hydroxysulfones from 8- and 10- functionalized camphor derivatives - MC CABE, THOMAS; GRAYSON, DAVID (Elsevier, 2011)
Some camphor-derived chiral allylic and benzylic sulfones in which the sulfonyl group is located at the C-10, C-9 or C-8 methyl groups of (+)-camphor were synthesized. The C-9 and C-8 substituted sulfones were obtained via Wagner-Meerwein rearrangements of the bicyclic camphor framework. On treatment with LDA, the C-10 and C-8 substituted sulfones cyclized with complete stereoselectivity, affording tricyclic ?-hydroxysulfones whose relative configurations were determined by X-ray crystallography. Tricyclic sulfones 23 and 24 underwent both ?-elimination and retro-aldol reactions on further exposure to base. Reduction of the carbonyl group of the C-10 substituted sulfones afforded exo-configured isobornyl sulfones with high stereoselectivity. Reaction of the lithiated isobornyl benzylsulfone 32 with benzaldehyde generated all four of the possible product diastereomers, of which three were isolated pure by chromatography. Attempted desulfonylation of these diastereomers failed to generate the desired optically active homobenzylic alcohols but the same sulfonyl carbanion trapping/desulfonylation sequence was successful in a model achiral series of compounds.
PUBLISHED
Keywords: Physical chemistry; Sulfones